Adsorption equilibria of water vapor on cork. - Lequin, Sonia; Chassagne, David; Karbowiak, Thomas; Gougeon, Régis; Brachais, Laurent; Bellat, Jean-Pierre (Journal of agricultural and food chemistry, 2010)
We report here for the first time a complete thermodynamic study of water vapor adsorption on crude cork powder and plate. Adsorption-desorption isotherms were accurately measured by thermogravimetry at 283, 298, and 313 K in a large range of relative pressure. Adsorption enthalpies were determined by calorimetry as a function of loading. Adsorption-desorption isotherms exhibit a hysteresis due to the swelling of the material. The influence of the presence of lenticels on the adsorption properties of cork is found to be negligible. A detailed analysis and interpretation of adsorption data allow proposal of an adsorption mechanism in two steps. (i) First, water adsorbs on hydrophilic sites constituted by hydroxyl and methoxyl groups. (ii) Then water adsorption continues by clusters formation around the hydrophilic sites.
The following values have no corresponding Zotero field: accession-num: 20192215
Keywords: Adsorption; Plant Bark; Plant Bark: chemistry; Quercus; Quercus: chemistry; Thermodynamics; water; Water: chemistry

Wine Oxidation and the Role of Cork - Karbowiak, Thomas; Gougeon, Régis D; Alinc, Jean-Baptiste; Brachais, Laurent; Debeaufort, Frédéric; Voilley, Andrée; Chassagne, David (Critical Reviews in Food Science and Nutrition, 2009)
The present review aims to show the state of the art of oxidation mechanisms occurring especially in white wines by taking into account knowledge from different fields in relation to the subject. It is therefore divided into three main parts. First, the mechanisms of oxidation relevant to white wine are discussed in the light of recent scientific literature. Next, the phenomenon of oxygen solubility in wine during the winemaking process, and in particular during bottling is stated theoretically as well as practically. Finally, the aspect of wine conservation after bottling is examined with respect to mass transfers which may occur through the closure, with a special emphasis on cork. Currently, specific physico-chemical properties still make cork closures the most important closure type used for the wine market, and especially for high quality wines. This final section will also include a review of studies performed on this subject, which have been analyzed in detail from a theoretical mass transfer point of view, in order to assess the extent to which the proposed scientific tools and the observed tendencies are relevant to progress in the understanding of the impact of this parameter on the behavior of a wine.
doi: 10.1080/10408390802248585
Keywords: Cork; diffusion; Oxygen; permeability; phenolic compounds; solubility; white wine